2019
DOI: 10.20944/preprints201908.0069.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ADCK2 Haploinsufficiency Reduces Mitochondrial Lipid Oxidation and Causes Myopathy Associated with CoQ Deficiency

Abstract: Fatty acids and glucose are the main bioenergetic substrates in mammals that are alternatively used during the transition between fasting and feeding. Impairment of mitochondrial fatty acid oxidation causes mitochondrial myopathy leading to decreased physical performance. Here, we report that haploinsufficiency of ADCK2, a member of the aarF domain-containing mitochondrial protein kinase family, in human is associated with liver dysfunction and severe mitochondrial myopathy with lipid droplets in skeletal musc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…S18 ). Previous studies with mice showed that oral CoQ 10 supplementation in wild-type animals can result in some uptake in the liver, ovaries and brown adipose tissue but perhaps not in other tissues despite sporadic positive reports [ 68 , 73 , 83 , [88] , [89] , [90] ]. In the present study, we directly compared oral feeding with LiQsorb at a ~1.6 times higher dose than that used with IV CF/CoQ 10 and observed only low plasma concentrations ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S18 ). Previous studies with mice showed that oral CoQ 10 supplementation in wild-type animals can result in some uptake in the liver, ovaries and brown adipose tissue but perhaps not in other tissues despite sporadic positive reports [ 68 , 73 , 83 , [88] , [89] , [90] ]. In the present study, we directly compared oral feeding with LiQsorb at a ~1.6 times higher dose than that used with IV CF/CoQ 10 and observed only low plasma concentrations ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CoQ. Furthermore, a recent study reported that haploinsufficiency of human CQD1 ortholog ADCK2 led to aberrant mitochondrial lipid oxidation and myopathy associated with CoQ deficiency 14 .…”
Section: Loss Of Cqd1 Confers Pufa Resistancementioning
confidence: 99%
“…CoQ10 is a mitochondrial coenzyme that is essential for the mitochondrial respiratory chain and ATP production. A set of at least 17 different genes synthesized CoQ10 in mitochondria [13][14][15][16][17]. Of these, mutations in ten genes (prenyl diphosphate synthase subunit 1 [PDSS1], PDSS2, COQ2, COQ4, COQ6, COQ7, COQ8A, COQ8B, COQ9, and AarF domain containing kinase 2) cause primary CoQ10 deficiency [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A set of at least 17 different genes synthesized CoQ10 in mitochondria [13][14][15][16][17]. Of these, mutations in ten genes (prenyl diphosphate synthase subunit 1 [PDSS1], PDSS2, COQ2, COQ4, COQ6, COQ7, COQ8A, COQ8B, COQ9, and AarF domain containing kinase 2) cause primary CoQ10 deficiency [17,18]. Many signs and symptoms of CoQ10 deficient patients are common among other mitochondrial diseases; these involve multiple organ systems and often show prominent neurologic and myopathic features.…”
Section: Introductionmentioning
confidence: 99%